Upaya Guru PAI dan Budi Pekerti Dalam Mengatasi Degradasi Moral Siswa di SMP Negeri 1 Kembaran - Septiani, Samroh; Hidayat, Imam (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to describe and analyze the efforts made by Islamic Religiors Education and Character Education teachers in addressing students’ moral degradation at SMP Negeri 1 Kembaran. The research focuses on identifying indication of students’ moral decline and axamining the strategies employed by PAI teachers to overcome it. This is a qualitative study using a descriptive field research. Data were collected through observation, in-depth interviews, and documentation. The main informats include PAI and Character Education teachers, students, and relate achool authorities. The research results indicate that the efforts of PAI teachers and Budi Pekerti in addressing the moral degradation of students involve implementing various strategies to shape character and improve the morals of students, such as role modeling, providing advice and motivation, habituating positive and religious activities, reinforcing religious values in learning, and collaborating with parents and the school community. These efforts significantly contribute to fostering the moral awareness of students and reducing deviant behavior in the school environment. This research can serve as a reference for developing moral education strategies, particularly for educators and education policymakers in designing character education programs rooted in Islamic values. Keywords : Islamic Religious Education and Character Teachers’ Efforts, Moral Degradation, Student